The impact of obesity and inflammation on metabolic risk factors for cardiovascular disease and type two diabetes in black and white South African women - Evans, Juliet P (Department of Human Biology, 2014)
[T]he overall aim of this thesis was to investigate the ethnic-specific role of inflammation in obesity and related metabolic risk factors associated with T2DM and CVD in apparently healthy black and white premenopausal South African women.